2022
DOI: 10.1108/pr-01-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

Colleagues' norms regarding work-related messages: their differential effects among remote and onsite workers

Abstract: PurposeResearch has shown that colleagues' norms promoting the need to respond quickly to work-related messages (CN) have a negative effect on work recovery experiences. In the present study, the authors examine the direct and indirect – through affective rumination and problem-solving pondering – effects of these norms on work–family conflict, family–work conflict and job satisfaction, and verify whether and how these associations differ between employees working onsite (n = 158) or remotely (n = 284).Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The repetitive thinking triggered by negative work events makes it di cult for individuals to psychologically and materially engage in family roles. It may even result in negative emotions spilling over from the workplace into the family space, leading to work-family con ict [44][45][46][47][48]. Park and Kim also proposed that the harmful effects of customer mistreatment extended into the personal life domain [49].…”
Section: Patient Mistreatment and Social Sharing Of Negative Work Eventsmentioning
confidence: 99%
“…The repetitive thinking triggered by negative work events makes it di cult for individuals to psychologically and materially engage in family roles. It may even result in negative emotions spilling over from the workplace into the family space, leading to work-family con ict [44][45][46][47][48]. Park and Kim also proposed that the harmful effects of customer mistreatment extended into the personal life domain [49].…”
Section: Patient Mistreatment and Social Sharing Of Negative Work Eventsmentioning
confidence: 99%
“…[38][39][40] Work-related rumination has been associated with both personal and relational well-being. 39,41,42 A daily diary study revealed that psychotherapeutic practitioners' daily work-related rumination is associated with bad mood, increased nervousness, and tiredness after work. 40 Similarly, elementary and secondary school teachers with high work-related rumination are more likely to have worse sleep quality and experience more negative mood.…”
Section: The Potential Indirect Role Of Work-related Ruminationmentioning
confidence: 99%
“…Job insecurity and workplace pressure increased work-family conflict for employees working fully from home and hybrid workers (Serdaroglu, 2021). Colleagues" norms of responding quickly to work-related messages has a direct association with higher levels of WFC and FWC for remote workers in the USA and British Isles (Gillet, Austin, Huyghebaert-Zouaghi, Fernet, & Morin, 2022a). Besides, workload and monitoring are connected to higher work-home interference (Wang et al, 2020).…”
Section: Organizational Forcesmentioning
confidence: 99%
“…Recovery which includes psychological detachment, relaxation, mastery, and control has a negative relationship with WFC (Ghislieri et al, 2021). Affective rumination mediates the association between colleagues" norms and employees" levels of FWC while problem-solving pondering and affective rumination mediate the relationship between colleagues" norms and employees" levels of WFC (Gillet et al, 2022a). Pandemic fears had a negative significant effect in predicting family interference with work for information technology (IT) employees working from home in Portugal (De Clercq & Pereira, 2022).…”
Section: Psychological Forcesmentioning
confidence: 99%